PRODUK DISTRO SEBAGAI IDENTITAS DARI REMAJA DI KOTA DENPASAR - Putra, I Made Satria; Tamim, Imron Hadi; Jaya, I Gede Kama (JURNAL ILMIAH SOSIOLOGI (SOROT), 2016)
ABSTRACT The aim of this research is to describe the fast growth of distro in Denpasar city, especially in Panjer village which become the pattern of the comsumption to the need of dressing among teenagers. The use of the distro products to young people in Denpasar city is more to show their self identification and to seek for a self acknowledgement in their social environment. It needs to be researched about the distro product as the identity of teenagers in Denpasar city. The finding of the research showed that the motivation of the consumption of the distro products among the teenagers in Denpasar city are (1) the uniqueness of the design and the brand, (2) the quality and the limited edition of the products, (3) up to date distro product, (4) distro product as the trend center (5) the influence of the peers, (6) the influence of the mass media. distro product meaning of the distro product among the teenagers in Denpasar city are the distro product as (1) a self identity, (2) social identity, (3) cultural identity. Â  Keywords; distro product, identity, teenagers in Denpasar city